Antiprotozoal Effect of Saponins in the Rumen Can Be Enhanced by Chemical Modifications in Their Structure - Ramos-Morales, Eva; de la Fuente, Gabriel; Duval, Stephane; Wehrli, Christof; Bouillon, Marc; Lahmann, Martina; Preskett, David; Braganca, Radek; Newbold, Charles J. (Frontiers in Microbiology, 2017)
The antiprotozoal effect of saponins is transitory, as when saponins are deglycosylated to the sapogenin by rumen microorganisms they become inactive. We postulated that the substitution of the sugar moiety of the saponin with small polar residues would produce sapogen-like analogues which might be resistant to degradation in the rumen as they would not be enzymatically cleaved, allowing the antiprotozoal effect to persist over time. In this study we used an acute assay based on the ability of protozoa to break down [14C] leucine-labelled Streptococcus bovis and a longer term assay based on protozoal motility over 24 h to evaluate both the antiprotozoal effect and the stability of this effect with fifteen hederagenin bis-esters esterified with two identical groups, and five cholesterol and cholic acid based derivatives carrying one to three succinate residues. The acute antiprotozoal effect of hederagenin derivatives was more pronounced than that of cholesterol and cholic acid derivatives. Modifications in the structure of hederagenin, cholesterol, and cholic acid derivatives resulted in compounds with different biological activities in terms of acute effect and stability, although those which were highly toxic to protozoa were not always the most stable over time. Most of the hederagenin bis-esters, and in particular hederagenin bis-sucinate (TSB24), hederagenin bis-betainate dichloride (TSB37) and hederagenin bis-adipate (TSB47) had a persistent effect against rumen protozoa in vitro, shifting the fermentation pattern towards higher propionate and lower butyrate. These chemically modified triterpenes could potentially be used in ruminant diets as an effective defaunation agent to, ultimately, increase nitrogen utilization, decrease methane emissions, and enhance animal production. Further trials in vivo or in long term rumen simulators are now needed to confirm the in vitro observations presented.